Antibacterial Activity of Leaves of Bamboo - Vijay kumar Singh; Rahul Shukla; Satish V; Shankul Kumar; Sumit Gupta; Ashutosh Mishra (International Journal of Pharma and Bio Sciences, 2010)
The Leaf of bamboo, belonging to family Gramine is used as anthhelmintic. Tabashir (bamboo manna) is stimulant, astringent, febrifuge, tonic, cooling, antispasmodic, and aphrodisiac. Antimicrobial activity of the successive extract of the fresh leaves of bamboo was evaluated against both Gram positive and Gram-negative bacterial strains by disc diffusion method. The results revealed that all extracts showed effective inhibitory action against S. aureas. The aqueous and ethnolic extracts showed very effective as compared to standard penicillin.